INTERNALISASI SOFT SKILLS MELALUI DIKLAT PAKEM DALAM RANGKA MENINGKATKAN MUTU PENDIDIKAN - Setiawan, Teriska Rahardjo (2012)
Education is a starting point and at the same time becomes an end of the various crises too. It is proved that the beginning of all crises has come from an attitude and ended by an attitude. An attitude of a person is determined by the way someone is being educated. Therefore, education is very important for changing a society. Many people believe that education plays important roles in the society, but education has many problems inherent in its process. In fact, at the micro level, such as in the class room, we find that a number of teachers are still incompetent in teaching. We know that they become the backbones of education and play very important roles in this matter. To overcome education problems is by improving the quality of the teachers. This has proved to be the most strategic effort of improving the quality of people, to be more creative, developed, empowered and powerful as a nation. A quality improvement program has been created and it is well known as PAKEM (Program Aktif, Kreatif, EfektifdanMenyenangkan). Since PAKEM being implemented, it was predicted that soft skills values have been internalized in it. They become part of important factors of teachers' competency. Thus, the research has been covering three folds as follows: Do the teachers who have been participated in PAKEM training has acquired soft skills? Have PAKEM influenced teachers soft skills? Have the ability of teachers soft skills influenced the quality of education? The trend of research is mostly of quantitative method, with the number of population sample amounted to 1.080 people, who have participated in PAKEM training conducted by The Directorate of Primary Education of the Ministry of Education and Culture of The Republic of Indonesia. Because the number of population was counted more than 1000, the researcher took only 10% up to 15 % from the total sample, in which only 223 people were taken as the research sample. The research findings shows that those teachers who participated in PAKEM training have obtained; Firstly, intrapersonal skills, kinesthetic skills, linguistic skills, interpersonal skills, musical skills, logic/mathematic skills, and visual skills. Secondly, PAKEM training has been able to influence the development of teachers' soft skills. Thirdly, the teachers' capability of soft skills, have been able to positively influence education quality. In this research it is taken that education quality is referred to students' attainments in academic year school exam. It was also found that there are some more factors other than soft skills which enable teachers to improve education quality. This has become a more in-depth study of this research that has enriched the analyses study into a type of qualitative method. Keywords: Soft Skills, PAKEM and Education Quality